The Development of A Sensor For Measuring Endurance Athletes While Doing A Kick in Tae Kwon Do - Faozan, Muhamad; Santosa, Imam; Annas, Mohamad (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research is to design and know the effectiveness of tools developed to measure endurance athletes when kicking in Taekwondo. The approach used in this research is Research and Development (R & D) method. Research subjects were athletes and coach. The subjects of the study were athletes and experts. Taekwondo expert validation results are good with a total score above 83, Expert validation Electro one is good with a total score of 86, For the two Electro experts stated both with a total score of 85. And also from the results of small-scale trials I obtained data that the product has not been effectively used. In large-scale trials the product is declared effective and can be used to measure the endurance of the athlete when kicking. The conclusions of this study resulted in an athlete endurance sensor product during a kick in Taekwondo, And also this product can be used for measuring endurance athletes when kicking. For trainers and athletes it is recommended to try the product as a tool to measure the endurance of the athlete while kicking in Taekwondo.